HUBUNGAN DUKUNGAN KELUARGA DENGAN RELAPS PADA PENDERITA SKIZOFRENIA DI WILAYAH KERJA PUSKESMAS MANTUP LAMONGAN - SITI PATONAH, SITI PATONAH (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
Schizophrenia is apsychotic disorderthat is chronic/recurrent disorder characterized bythe severity of personality, distortionof reality and inability to function in everyday life. Schizophrenia is often chronic disease and relapse, so that patients require therapy/treatment for long.Cross Sectional study approach. Independent variables were family support, the dependent variable was the incidence of relapse. The samples studied were 26 people. Statistical analysis with Spearman's Rho correlation.Based on Spearman'sRho correlation results with a significance 0,022 (p < 0,05),, means there isa significant negative relationship between family support with a Relapses in patients with schizophrenia at the   health center Mantup Lamongan District.In carrying out nursing care, nurses need to involve the family's role as providing information about the disease of schizophrenia to the family, provide information on how to take medicine to the families, referring families to bring people with schizophrenia to the health service if a relapse and gives understanding to the families to accept people with schizophrenia during  the house. Keywords: FamilySupport, Relapsesin patients withschizophrenia